Curvature of unsymmetric cross-ply laminates: Combined effect of thermal stresses, microcracking, viscoplastic and viscoelastic strains. (February 2017) - Varna, Janis; Persson, Magnus; Claudel, Florian; Hajlane, Abdelghani
Curvature of unsymmetrical [0/90] specimens caused by thermal stresses changes if the specimen is subjected to large axial strains introducing intralaminar cracks in the 90-layer. It is shown that the large curvature reduction can not be explained by cracking related stress release only. The large irreversible viscoplastic strains introduced during the axial tensile loading (with 5 min holding at high strain for crack counting) give the main contribution to the curvature change. The effect of transient viscoelasticity (VE) was found to be of minor significance. Simple approach based on effective damaged layer stiffness and constant irreversible strain is used in the framework of laminate theory to extract the viscoplastic and VE strains from experimental curvature data. The obtained fitting expressions for viscoplastic- and VE-strain development are successfully used to describe curvature change in [0/902 ] laminate subjected to the same test procedure. It is suggested that the used curved beam tests could be efficient to characterize the viscoplastic strain development in the thin 90-layers.